A modified percutaneous atrial balloon septoplasty for difficult transseptal puncture. Issue 28 (16th July 2021) - Wang, Siyu; Zhao, Lei; Wang, Yuxing; Yin, Xiandong; Yang, Xinchun; Liu, Ye
Abstract : Abstract: Catheter ablation of atrial fibrillation sometimes encounters difficulty in passing the interatrial septum. This study reports a modified percutaneous atrial balloon septoplasty with short balloon to gain access to left atrium (LA) during challenging transseptal puncture (TSP). We retrospectively analyzed 20 patients (61.75 ± 7.31 years, 45% male) who received modified percutaneous atrial balloon septoplasty from August 2015 to October 2018. Soft-headed balance middle weight (BMW) guidewire was inserted into left superior pulmonary vein (LSPV) and short non-compliant balloon (15 mm in length and 4.0 or 5.0 mm in diameter) was used for atrial balloon septoplasty (ABS). Interatrial septum was located with inflated balloon and contrast "Hitting Wall" sign. All patients were followed-up for iatrogenic atrial septal defect (iASD) and other related complications. ABS and LA access were performed successfully without complications in all 20 patients. Time needed for ABS was correlated to the number of prior TSP ( P = .007). During the 6-month follow-up, no remaining iASD was found by echocardiography. For atrial fibrillation patients with difficulty in passing the interatrial septum, this modified percutaneous ABS might be an alternative strategy which is safe to obtain transseptal access without short or long term complications.